Effectiveness test of dental hypnosis monitoring device - Kusmayanti, Suci; Yubiliana, Gilang; Abdurrochman, Andri; Ramdani, Muhamad Lutfi; Fauzan, Naufal Hilmi (Universitas Padjadjaran, 2021)
Introduction: Modified Dental Anxiety Scale (MDAS) questionnaire is a simplified 5-point scale answering scheme, ranging from not anxious to extremely anxious. Anxious level can be reduced through dental hypnosis. Dental hypnosis monitoring device is an innovative device due to the Student Creativity Program Universitas Padjadjaran. The device can monitor a patient's consciousness by monitoring the brain wave level so that dentists can determine what steps to take when handling a patient. The effectiveness of this device has not been tested yet. This study was aimed to determine the effectiveness of the dental hypnosis monitoring device. Methods: A descriptive study was conducted on this study population, which was all the patients of Universitas Padjadjaran Dental Hospital (RSGM Unpad) who filled out the Modified Dental Anxiety Scale (MDAS) questionnaire. The sample criteria were people with moderate to high MDAS score and aged 17 years or above. Twenty-four people were obtained through consecutive sampling in one day. The study was held at Universitas Padjadjaran Dental Hospital by comparing the dental hypnosis monitoring device's performance with opinion from the dental hypnosis expert. Results: The overall success rate for the dental hypnosis monitoring device's effectiveness was 100% since the LED was always lit green during the hypnosis session, which was following the dental hypnosis expert assessment during processes. Conclusion: Effectiveness of the dental hypnosis monitoring device was proven to be 100% effective.